The value of stereotactic biopsy of primary and recurrent brain metastases in the era of precision medicine - Katzendobler, Sophie; Do, Anna; Weller, Jonathan; Rejeski, Kai; Dorostkar, Mario M.; Albert, Nathalie L.; Forbrig, Robert; Niyazi, Maximilian; Egensperger, Rupert; Tonn, Joerg-Christian; von Baumgarten, Louisa; Quach, Stefanie; et al. (Frontiers in Oncology, 2022)
Brain metastases (BM) are the most frequent intracranial tumors with increasing incidence. Many primary tumors are currently treated in protocols which also include targeted therapies. Molecular markers are gaining increasing importance. In cases with diagnostic uncertainty, both in newly diagnosed or recurrent BM, stereotactic biopsy (STX) is an alternative to microsurgical resection particularly whenever resection is deemed not to be safely feasible. This retrospective study aimed to analyze both diagnostic yield and safety of an image-guided frame based STX. Our neurosurgical data base was searched for any surgical procedure for suspected BM between January 2016 and March 2021. Of these, only patients with STX were included. Clinical parameters, procedural complications, histology and molecular signature of the tissue obtained were assessed. Overall, 467 patients were identified including 234 (50.1%) with STX. Median age at biopsy was 63.7 years (range 28.7 – 87.2 years). MRI was used for frame-based trajectory planning in every case with additional PET-guidance in 38 cases (17.9%). In total, serial tumor probes provided a definite diagnosis in 230 procedures (98.3%), in 4 cases, no diagnosis could be defined. 114 (48.7%) had newly diagnosed and 46 (19.7%) progressive BM. Pseudoprogression was verified in 46 cases which was always confirmed by further course of disease. 24 cases had to be excluded due to non-metastatic histology, leaving 206 cases for further analyzes. Metastatic tissue was found most frequently from lung cancer (39.8%), followed by breast cancer (9.2%), and malignant melanoma (7.3%). Other entities included gastrointestinal cancer, squamous cell cancer, renal cell carcinoma, and thyroid cancer. In 9 cases (3.8%), the tumor origin could not be identified (cancer of unknown primary). In total, molecular genetic analyzes was successful in 137/144 (95.1%). Additional next generation sequencing revealed conclusive results in 12/18 (67%) cases. Relevant peri-procedural complications were seen in 5 cases (2.4%). No permanent morbidity or mortality was noted. Frame-based STX is a safe procedure with a high diagnostic yield in BM. Differentiation between tumor recurrence and post-therapeutic changes is reliably achieved. The value of a comprehensive molecular characterization based on the stereotactic samples offers a high potential for precision medicine of BM.